Size and degree of protection of native forest remnants drive the local occupancy of an endangered neotropical primate - Lins, Poliana G. Alves de Souza; Ribeiro-Júnior, José W. [UNESP]; Peres, Carlos A.; Penha, Jerry (Wiley, 2022)
Although the species–area relationship is well known, it may interact with and be augmented or cancelled out by other factors, such as local human disturbance. We used data on site occupancy of the Endangered blonde capuchin monkey (Sapajus flavius) based primarily on a standardized program of local interviews to model the influence of past human disturbance on the occurrence of this species across remaining forest patches of northeastern Brazil within the Atlantic Forest and Caatinga biomes. To do so, we assessed environmental covariates that best represent the history of human impacts. We then used single-species occupancy models to assess site occupancy, while controlling for detection error during sampling. Surprisingly, we obtained a higher occupancy rate in the more arid Caatinga remnants than in the more mesic Atlantic Forest. Habitat patch size, history of site protection, and annual precipitation were the best predictors of local occupancy. Historical human disturbance, including subsistence hunting, has exerted considerable impact on the modern distribution of the blonde capuchin, whose geographic range largely spans a region historically lacking any wildlife protection. Matrix vegetation structure across the Caatinga, which so far has averted large-scale mechanized agriculture, also creates a benign landscape that likely benefits contemporary capuchin occupancy. Local extinctions of this endangered primate will most likely continue unabated unless a ban on hunting in remaining Atlantic Forest and Caatinga fragments can be enforced.
Keywords: blonde capuchin monkey; fragmentation; hunting; local interviews; occupancy models